The Problem of Violating The Law on Information and Electronic Transactions in Democracy Country - Rohmah, Elva Imeldatur; Ilmiyah , Zainatul; Ningtyas , Mega Ayu (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
Law Number 11 of 2008 concerning Information and Electronic Transactions as amended by Law Number 19 of 2016 (ITE Law) is a law that regulates all matters concerning information technology applicable in Indonesia. As a democratic country, Indonesia upholds and respects freedom. In reality, the ITE Law creates many problems in the midst of society, because it is often used as a tool to limit freedom of speech and opinion. The results of this study indicate that the presence and implementation of the ITE Law which is considered to silence freedom of opinion and expression which is one of the pillars of democracy for social media users, is actually not all true. The existence of the ITE Law actually presses all parties to be more careful in their attitudes and expressions on social media. So that the negative impact or violation of the rights of freedom of others and other violations in the cyber world can be avoided. Then the freedom of opinion and expression can run well.